Measurements of tractor power parameters using GPS - M. Pexa; M. Cindr; K. Kubín; V. Jurča (Research in Agricultural Engineering, 2011)
Understanding of the power parameters of an agricultural energy device (tractor) is very important in relation to the final outcome. This understanding is necessary to achieve high performance in combination with low economic costs and favourable ecological conditions. Monitoring the progress of power parameters (torque and engine power) is possible mainly by dynamometer, which is not affordable for common undertaking. The option of using GPS receiver to determine the torque of the engine and its backup torque seems to be an appropriate option. The data thus collected will contribute to the timely detection of defects, and thus prevent the emergence of economic and ecological consequences that are related to the tractor engine.